USING PROJECT-BASED LEARNING TO PROMOTE DIGITAL LITERACY: STUDENTS’ PERCEPTIONS - Nuraeni Nuraeni; Husnee Binhayeekhonoh; Sekar Hayuning Nur Ramadhani; Fadia Holisah; Deviana Maulidia Gusnadi (English Didactic, 2022)
Project-based learning has been studied and believed as one of the approaches that are effective to be used in teaching. This study aimed at finding out students’ perceptions of the use of PjBL in promoting digital literacy. The study was framed under a qualitative case study in which observation, questionnaire, and interview were administered. The data was taken from a private university in west java. The findings show that students have positive perceptions of PjBL. It is believed that PjBL has helped students not only in achieving the goal of the learning process but also in extending their knowledge and point of view. Further study on a bigger scale on PjBL is suggested.